TH Cells and Cytokines in Encephalitogenic Disorders - Krishnarajah, Sinduya; Becher, Burkhard (Frontiers in Immunology, 2022)
The invasion of immune cells into the central nervous system (CNS) is a hallmark of the process we call neuroinflammation. Diseases such as encephalitides or multiple sclerosis (MS) are characterised by the dramatic influx of T lymphocytes and monocytes. The communication between inflammatory infiltrates and CNS resident cells is primarily mediated through cytokines. Over the years, numerous cytokine networks have been assessed to better understand the development of immunopathology in neuroinflammation. In MS for instance, many studies have shown that CD4+ T cells infiltrate the CNS and subsequently lead to immunopathology. Inflammatory CD4+ T cells, such as TH1, TH17, GM-CSF-producing helper T cells are big players in chronic neuroinflammation. Conversely, encephalitogenic or meningeal regulatory T cells (TREGs) and TH2 cells have been shown to drive a decrease in inflammatory functions in microglial cells and thus promote a neuroprotective microenvironment. Recent studies report overlapping as well as differential roles of these cells in tissue inflammation. Taken together, this suggests a more complex relationship between effector T cell subsets in neuroinflammation than has hitherto been established. In this overview, we review the interplay between helper T cell subsets infiltrating the CNS and how they actively contribute to neuroinflammation and degeneration across CNS diseases. Importantly, in this context, we will especially focus on the current knowledge regarding role of TH1, TH17 and GM-CSF producing cells.